Inhibition of cancer cell growth by ruthenium complexes. Issue 1 (December 2016) - Iida, Joji; Bell-Loncella, Elisabeth; Purazo, Marc; Lu, Yifeng; Dorchak, Jesse; Clancy, Rebecca; Slavik, Julianna; Cutler, Mary; Shriver, Craig
Abstract Background Previous studies suggest that certain transition metal complexes, such as cisplatin, are efficacious for treating various cancer types, including ovarian, lung, and breast. Methods In order to further evaluate ruthenium (Ru) complexes as potential anti-cancer agents, we synthesized and evaluated Ru-arene complexes. Two complexes with the general formula [Ru (η 6 -p -cym) (N–N) Cl]+ were tested for their abilities to inhibit cancer cells. Results The complex witho -phenylenediamine as the N–N ligand (o -PDA) significantly inhibited growth of breast (MDA-MB-231, MCF-7, SKBR-3, and SUM149), lymphoma (Raji), melanoma (Bowes), and osteosarcoma (HT1080); however, the complex witho -benzoquinonediimine (o -BQDI) was ineffective except for SUM149. In contrast, o -PDA failed to inhibit growth of human breast epithelial cells, MCF-10A. Treatment of MDA-MBA-231 cells witho -PDA resulted in a significant reduction of productions of PDGF-AA, GM-CSF, and VEGF-A proteins at the transcriptional levels. Finally, we demonstrated thato -PDA synergistically inhibited MDA-MB-231 cell growth with cyclophosphamide but not doxorubicin or paclitaxel. Conclusion These results suggest that Ru-arene complexes are promising anti-cancer drugs that inhibit progression and metastasis by blocking multiple processes for breast and other types of cancer.